2008
DOI: 10.1016/j.bbrc.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The ferrous-oxy complex of human aromatase

Abstract: In this communication, we document the self-assembly of heterologously expressed truncated human aromatase (CYP19) into nanometer scale phospholipids bilayers (Nanodiscs). The resulting P450 CYP19 preparation is stable, and can tightly associate the substrate androstenedione to form a nearly complete high-spin ferric protein. Ferrous CYP19 in Nanodiscs was mixed anaerobically in a rapidscan stopped-flow with atmospheric dioxygen and the formation of the ferrous-oxy complex observed. First order decay of the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…As of the end of 2008, the list of membrane protein reconstituted into Nanodiscs for functional studies include the cytochromes P450 (Baas et al, 2004; Bayburt and Sligar, 2002; Civjan et al, 2003; Das et al, 2007; Das, 2009; Denisov et al, 2006; Denisov et al, 2007; Duan et al, 2004; Grinkova et al, 2008; Kijac et al, 2007; Nath et al, 2007b) bacteriorhodopsin as a monomer and trimer (Bayburt et al, 2006; Bayburt and Sligar, 2003), G-protein coupled receptors as monomers and dimers (Bayburt et al, 2007; Leitz et al, 2006; Marin et al, 2007), other receptors (Boldog et al, 2006; Boldog et al, 2007; Mi et al, 2008), toxins (Borch et al, 2008), blood coagulation protein tissue factor (Morrissey et al, 2008; Shaw et al, 2007), protein complexes of the translocon (Alami et al, 2007; Dalal et al, 2009), and monoamine oxidase (Cruz and Edmondson, 2007). The potential of Nanodiscs is exemplified by their utility in diverse biochemical and biophysical methodologies, including solid state NMR (Kijac et al, 2007; Li et al, 2006), single molecule fluorescence experiments (Nath et al, 2008), and solubilizing functional receptors (Bayburt et al, 2007; Boldog et al, 2007; Leitz et al, 2006; Mi et al, 2008).…”
Section: Reconstitution Considerationsmentioning
confidence: 99%
“…As of the end of 2008, the list of membrane protein reconstituted into Nanodiscs for functional studies include the cytochromes P450 (Baas et al, 2004; Bayburt and Sligar, 2002; Civjan et al, 2003; Das et al, 2007; Das, 2009; Denisov et al, 2006; Denisov et al, 2007; Duan et al, 2004; Grinkova et al, 2008; Kijac et al, 2007; Nath et al, 2007b) bacteriorhodopsin as a monomer and trimer (Bayburt et al, 2006; Bayburt and Sligar, 2003), G-protein coupled receptors as monomers and dimers (Bayburt et al, 2007; Leitz et al, 2006; Marin et al, 2007), other receptors (Boldog et al, 2006; Boldog et al, 2007; Mi et al, 2008), toxins (Borch et al, 2008), blood coagulation protein tissue factor (Morrissey et al, 2008; Shaw et al, 2007), protein complexes of the translocon (Alami et al, 2007; Dalal et al, 2009), and monoamine oxidase (Cruz and Edmondson, 2007). The potential of Nanodiscs is exemplified by their utility in diverse biochemical and biophysical methodologies, including solid state NMR (Kijac et al, 2007; Li et al, 2006), single molecule fluorescence experiments (Nath et al, 2008), and solubilizing functional receptors (Bayburt et al, 2007; Boldog et al, 2007; Leitz et al, 2006; Mi et al, 2008).…”
Section: Reconstitution Considerationsmentioning
confidence: 99%
“…S1 (25). This approach has been shown to produce well-behaved assemblies of this and other membrane-bound enzymes, with the important advantage that such entities effectively enhance the stabilities of the dioxygen adducts of these enzymes (25,26), allowing them to be efficiently prepared and quickly trapped at liquid nitrogen temperature. Indeed, our previously reported resonance Raman (rR) spectroscopy studies (27), which focused on the trapped dioxygen adducts of CYP17A1 bound with its natural substrates, clearly showed that H-bonding interactions between the Fe-O-O fragments and active site residues, including bound substrates, produce telltale vibrational frequency shifts that effectively differentiate functionally significant H-bonding interactions to the proximal (p) or terminal (t) atoms within the Fe-O p -O t fragment (28,29).…”
Section: Significancementioning
confidence: 99%
“…For example, the Arrhenius activation energy for autoxidation of CYP3A4 saturated with the substrate testosterone is 22 kcal/mol (48), and for autoxidation of CYP19 with androstenedione, it is 18 kcal/mol (51). Contrary, the O 2 and CO binding rates have significantly lower activation energies in the range 6 – 9 kcal/mol, as documented for several heme proteins (52-55).…”
Section: Introductionmentioning
confidence: 99%